Outcome of first relapse of Hodgkin lymphoma: Single Institution experience - Najma Shaheen; Ata Ur Rehman Maaz; Muhammad Saghir Khan (Journal of the Pakistan Medical Association, 2020)
Objectives: 1:To determine outcome of first relapse of Hodgkin Lymphoma with standard dose chemotherapy. 2: To identify the prognostic factors predicting survival outcome in pediatric relapsed Hodgkin lymphoma. Methods: This was a retrospective analysis of 43 patients with HL who relapsed at least 3 months after completion of initial treatment from January 2001 to December 2010. Probabilities of OS, EFS and cumulative incidence were calculated by Kaplan-Meier method. Log rank tests were used to compare survival curves and p-value<0.05 was considered significant Results: Median age at relapse was 11± 3.3 years. In 72% of patients EPIC chemotherapy was employed. Median follow up of this cohort was 62 months (range 4-187 months). OS and EFS at 10 years was 54% and 35% respectively. On univariate analysis; initial disease stage (p=0.021), stage at relapse (p=0.003), treatment protocol (p=0.005), treatment responsiveness at initial two cycles of salvage chemotherapy (p=0.002) and at the end of treatment assessment (p=0.0009) were statistically significant factors. Multivariate cox regression analysis revealed disease stage at relapse (p=0.004), chemotherapy regimen (p=0.025) and end of treatment disease evaluation (p=0.005) as the statistically significant variables. Conclusion: First relapse of HL is potentially salvageable with standard dose chemotherapy with/without radiation. The patients with early stage at relapse and those with chemo-responsiveness can be effectively treated without ASCT. We observed improved outcome with EPIC chemotherapy regimen for the patients who had DFI of more 2 years.